2020
DOI: 10.1590/1678-5150-pvb-6484
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the reference interval of the C-reactive protein/albumin ratio and its efficiency, CRP and albumin as prognostic markers in dogs

Abstract: The objective of this research was to creates a reference interval for C-reactive protein (CRP)/albumin ratio (CAR) in the canine species and to analyze the potential of CRP, albumin and the relationship between both, to serve as indicators of disease severity, length of hospital stay (LoS) and mortality in this species. For this, an outcome study was conducted in a Veterinary Teaching Hospital in southern Brazil. One hundred ninety dogs were included randomly, without distinction of gender, age, or breed, fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Compared with the plasma albumin concentration, the plasma PAB concentration was significantly decreased in group B. Albumin is a negative APP synthesized in hepatocytes ( 18 ). The reasons for the deceased plasma albumin concentration in inflammation have been shown to be due to leakage from the intravascular compartment caused by increased vascular permeability, denaturation at sites of inflammation, reduced synthesis in the hepatic parenchyma, and degradation of albumin bound to toxins ( 12 , 18 , 27 ). Although albumin has been reported to be a useful, easy, and inexpensive parameter for detecting inflammatory diseases in dogs, it is a slow-reacting negative APP in dogs ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the plasma albumin concentration, the plasma PAB concentration was significantly decreased in group B. Albumin is a negative APP synthesized in hepatocytes ( 18 ). The reasons for the deceased plasma albumin concentration in inflammation have been shown to be due to leakage from the intravascular compartment caused by increased vascular permeability, denaturation at sites of inflammation, reduced synthesis in the hepatic parenchyma, and degradation of albumin bound to toxins ( 12 , 18 , 27 ). Although albumin has been reported to be a useful, easy, and inexpensive parameter for detecting inflammatory diseases in dogs, it is a slow-reacting negative APP in dogs ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be useful as an indicator in cases in which rapid therapeutic intervention must be assessed. Recent human and veterinary medicine studies have revealed that evaluating both positive APPs and negative APPs in patients may be better for confirming the degree of inflammation and predicting survival (11,27,40,41). For instance, during inflammation, the plasma CRP concentration increases, while the PAB concentration decreases.…”
Section: Discussionmentioning
confidence: 99%